The key to temperate savanna restoration is to increase plant species richness reasonably - Dou, Pengpeng; Miao, Zhengzhou; Wang, Jie; Huang, Jing; Gao, Qian; Wang, Kaili; Wang, Kun (Frontiers in Environmental Science, 2023)
Changes in species composition and diversity-productivity relationships during vegetation succession are of great significance for the restoration of degraded grasslands. However, the human intervention of grassland restoration mostly considers the single ecological (diversity) or production (biomass) function of grasslands, and does not fully consider the relationships between the two to improve the restoration effects. In this study, three vegetation types (desert grassland, sandy grassland and temperate savanna) were considered to simulate the three stages of restoration of degraded temperate savanna (early, middle and late restoration). Changes in species composition, diversity, and diversity-productivity relationships during the temperate savanna restoration were explored through spatiotemporal substitution. The results showed that with the progress of succession, xerophytes decreased significantly, mesophytes and hygrophytes increased, C4 plants decreased gradually, and C3 plants increased. The change of species richness was the main reason for community differences in the process of community succession, and species replacement mainly occurred between communities in the early and middle stages of succession. Species richness increased significantly from early to late stage of restoration. Latitude was significantly negatively correlated with species diversity. In the process of vegetation restoration, the impact of species richness, Pielou’s evenness, and β-diversity on biomass gradually developed positively and continued to increase, while the Simpson index showed the opposite effect. This study provides references for the restoration of temperate savanna and emphasizes the ecological and productive functions of the grassland should be taken into account in the restoration strategy.